Study on occurrence of the IVS8-5T allele of the CFTR gene in Ukrainian males with spermatogenesis failure - Fesai, O.A.; Kravchenko, S.A.; Zinchenko, V.M.; Livshits, L.A. (Вiopolymers and Cell, 2010)
Aim. To study the IVS8-5T allele of the CFTR gene and it is involvement in spermatogenesis failure in men with azoospermia and oligozoospermia. Methods. The IVS8-nT polymorphism was analyzed by PCR followed by «A.L.F.-express» fragment analysis in the infertile men group, consisting of 113 azoospermic and 217 oligozoospermic patients, and the control group of 150 fertile men with proven paternity. Results. The frequency of the IVS8-5T allele among infertile males was higher than in controls. A statistically significant difference (P < 0.05) was observed in the frequencies of the IVS8-5T allele in azoospermia patients (5.3 %) when compared with the control group (2.0 %). Conclusions. The IVS8-5T allele of the CFTR gene contributes to spermatogenesis failure and/or sperm maturation.